Pengembangan Sistem Informasi Manajemen Aset Kantor Berbasis Cloud Computing di Universitas Pamulang untuk Efisiensi Operasional - Femilda Aprilia; Veivi Novi Lestari; Junjung Adi Prasetyo Lenggogeni (Journal of Information Technology and Informatics Engineering, 2025)
This study aims to develop a cloud computing-based canteen asset management information system at Pamulang University to improve operational efficiency and optimize asset management. The rapid development of information technology drives digital transformation in various sectors, including campus facilities such as canteens, which demand high efficiency and accuracy in asset management. Using the System Development Life Cycle (SDLC) approach through needs analysis, system design, conceptual implementation, and theoretical evaluation based on literature studies, this study identifies problems such as manual recording, difficulty in real-time monitoring, and lack of automated reporting. The proposed system utilizes a Software as a Service (SaaS) architecture for high scalability and multi-platform access, providing digital asset catalog features, inventory management, real-time asset tracking, and analytical dashboards to monitor canteen operational performance. The implementation of cloud computing is expected to improve data security, reduce IT infrastructure costs, and facilitate access to asset information from anywhere. The concept of this system is designed to support various user roles, such as canteen staff and university management, and provides a framework that can be applied to other similar facilities.